المشاركة المتناقصة وتطبيقاتها في المصارف السودانية : دراسة حالة /‏ - إدريس، ست العيلة محمد السلاوي (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2015)
This research focusses on the study and analysis of al-Musharakah al-Mutanaqisah (Diminishing Partnership) and its application in Sudanese financial institutions. The burgeoning modern banking system necessitates looking for more resilient tools for the development of economic systems in the country particularly in the current enormous changes taking place in the banking industry which require a rethinking or perhaps reinventing reliable investment methods that could meet the needs of various financing sectors in the country. This research, therefore, attempts to examine numerous issues, whether legal or practical relating to al-Musharakah al-Mutanaqisah (Diminishing Partnership) as is applied in Sudanese banks. The research aims at investigating al-Musharakah al-Mutanaqisah and how different it is from other Islamic financing transactions, whether modern or traditional, as dealt with in the Islamic jurisprudence. In carrying out this research, the researcher applied multiple research methodologies ranging from that of pure doctrinal and non-doctrinal to that of descriptive and inductive approaches. Furthermore, an attempt was made to conduct fieldwork to collect the relevant data. Extensive of personal interviews with experts in the field were among the methods of collecting data. Finaly result, it was noted that despite the importance of al-Musharakah al-Mutanaqisah it was found to be less ventured into compared to other methods of transactions mainly because it is a comparatively new concept in bank dealings and many lack adequate knowledge of it.